METHODOLOGY FOR TEACHING PHYSICS THROUGH INTEGRATION WITH MILITARY-TECHNICAL TRAINING - Xaydar Ikramovich Ergashev; Professor I. G. Tursunov (Journal Park Publishing, 2025)
This article analyzes the theoretical and practical foundations of teaching physics based on integration with the discipline of military-technical training. The study also highlights the didactic potential of integrated educational technologies, the methodology of organizing training sessions, and their significance in developing the cognitive abilities of students (cadets). The research results demonstrate that integrating physics with military-technical disciplines contributes to the development of cadets’ practical thinking, the formation of their professional competencies, and enhances their interest in military-technical training.
Keywords: integrated education, physics, military-technical training, teaching methodology, technical thinking, practical training, interdisciplinary logical correlation.